AS YOU WRITE, IT HELPS YOU LISTEN: AN EXPERIMENT IN TOEFL PREPARATION CLASS - Ismail, Nyak Mutia; Zalha, Fera Busfina (Institut Agama Islam Negeri Imam Bonjol Padang, 2018)
This study was conducted as an aim to test whether using the technique named keeping-journals during the TOEFL preparation class is beneficial for the listening section part A of the test. As proposed by Hiemstra (2001) that in keeping journals technique, learners deliberately record their progress of learning, focusing on both their strengths and weaknesses. From this step, they can rigorously employ the metacognitive awareness and strategy awareness they have owned; or, they cantry to build ones (Oxford, et.al, 2004; Palfreyman, 2005). The result is considered essential since, practically, TOEFL tutors need to bring TOEFL learners to keep track on their learning rate on their own; hopefully, the result canbestsuitthe theoretical gap since there have been only few experimental studies conducted on Listening Section of TOEFL through journal-keeping. The quantitative pretest-posttest method used in this study involves single-group design consisting of 36 fifth semester college students at Syiah Kuala University, Aceh, Indonesia. The findings approved that the Ha is accepted for the tvalue is 1.90 (df 34, α=0.05, -2.02 ≤ t ≥ 2.02 ). It is also sigificant for the sigvalue is 0.7 (sigvalue ≥ α=0.05). In conclusion, the technique does help the learners in tackling problems they face in Listening section on TOEFL part A as it enhances their listening performance, attitude, and motivation.